Perawatan Spiritual Pasien Di Ruang Intensive Care Unit: Narrative Review - Suhartini, Suhartini; Pasole, Fetty Yublika; Sobirin, Mochamad Ali (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Nursing services worldwide today strive to incorporate a holistic approach, where individuals are regarded as complete beings encompassing biological, psychological, social, cultural, and spiritual dimensions. Within the context of intensive care units (ICUs), spiritual care is recognized as a fundamental element that can foster hope, provide a sense of life's purpose, and alleviate anxiety in patients. This research aimed to gain insight into the provision of spiritual care for ICU patients and utilized a narrative review methodology. Searches were conducted in clinical databases such as Scopus and ProQuest, using keywords like "intensive care unit AND patients AND psychiatric care AND spirituality." The selected articles adhered to inclusion criteria, pertained to the subject matter, and were published within the last seven years (2016-2022). In total, 11 articles were included as primary references in this study. The findings of this research reveal that ICUs offer three categories of spiritual services to patients: tailored spiritual services that address individual needs, spiritual support provided by the patient's family, and spiritual support delivered by healthcare professionals. This study underscores the multiple facets of spiritual care that benefit ICU patients, encompassing the recognition and response to their spiritual needs, the assistance of family members, and the support provided by the medical team. All of these components contribute positively to the recovery of ICU patients and meet their spiritual requirements.